Teaching Students with Special Needs in the 21st Century Classroom - Mayberry, Sally Cox,; Lazarus, Brenda Belson, (Rowman & Littlefield Publishers, 2002)
The inclusive schools movement has been around since the mid 1980s, yet many teachers find themselves ill-equipped to make the transition. This superb book offers information, guidance, and training ranging from history of the inclusion movement to recommended activities for use with students. The authors draw upon their personal experiences as classroom teachers and describe ways of implementing curriculum change, grading procedures, partnering with parents, and other key strategies to assist the teacher in setting up a successful inclusive classroom to meet the needs of all students in the 21st century.